The role of itinerant teachers of reading : a thesis presented in fulfilment of the requirements for the degree of Master of Education at Massey University - Phillips, Rosalie Kay (Massey University, 1980)
The position of Itinerant Teacher of Reading was established following a successful pilot scheme in 1974. The Department of Education indicated that the function of the itinerant teachers was to help alleviate the problem of children who experience severe difficulties in learning to read. Departmental instructions to Education Boards were couched in general terms to allow the Boards some latitude in defining and establishing the role. This study researches the role of Itinerant Teachers of Reading. The major objectives of the study were to describe the underlying purposes of the itinerant service and to clarify the role of Itinerant Teachers of Reading. The literature discussing children at risk in reading reveals a similarity of opinions on the alleviation of the problem. New Zealand authorities on reading agree that there is a minority group of children who require intensive regular and individualised instruction to improve their reading ability. Also apparent is the tendency for the varied methods of instruction to be focussed closely upon text reading rather than isolated skills acquisition. To ascertain the ways in which itinerant teachers were dealing with children at risk information was gathered via a questionnaire from all Itinerant Teachers of Reading in New Zealand. From their responses emerged three clearly discernible role patterns which ranged from an advisory type role to that of a travelling reading clinician. More detailed information was obtained by interviewing six of the fifteen itinerant teachers and observing four of the teachers at their work. To gain a balanced viewpoint of the itinerant service a second questionnaire solicited opinions and data from a representative adviser and an inspector from each of the ten Education Boards. In general their opinions of the true function of itinerant teachers supported their Board's itinerant teacher(s). Some variation between the methods of teaching advocated by this group and those used by the itinerant teachers was apparent. An examination of Departmental documents followed by a lengthy correspondence with personnel involved in the pilot scheme produced a description of the initial purposes of the itinerant service. The first itinerant teachers were required to establish a pool of resource teachers in schools by training selected teachers in appropriate teaching skills. Although the study is a descriptive one, the opinions expressed by the questionnaire respondents were discussed and presented as recommendations for possible future action. The recommendations encompassed the spheres of communications, service support, role clarification and standardisation, and accountability. The study concludes with a brief note on possible future evaluation.
Keywords: New Zealand Remedial teaching; Reading